The Influence of Service Quality (Ojek Online) on Customer Satisfaction in Medan - Mariska Sisilia; Jhon Piter; Melva Melany Sitompul (Elektriese: Jurnal Sains dan Teknologi Elektro, 2024)
This study was conducted to understand how service quality is influenced by responsiveness, responsibility, physical evidence, empathy, and reliability for customer satisfaction. These studies collected data using the questionnaire method and surveyed 30 consumers with experience using online taxi services in Medan City. Data analysis was done using a multiple regression method using SPSS software version 25. Two factors, namely responsiveness and satisfaction, can increase satisfaction. At the same time, it is impossible to improve consumer satisfaction in the other three dimensions of service quality: responsible, physically tested, and empathetic. This research is classified as explanatory research, which aims to elucidate, outline, and offer empirical data or a comprehensive understanding of the impact of the independent variable on the dependent variable defined in this study. The study's population comprises all users of online motorcycle taxi services in Medan. The findings indicate that service quality dimensions, specifically responsiveness and reliability, impact customer satisfaction among online motorcycle taxi users in Medan. In contrast, the aspects of service quality related to guarantees, fictitious evidence, and empathy do not significantly affect customer satisfaction for online motorcycle taxi services in Medan City.